Main Complications Related to COVID-19 in Pregnancy (Research, Society and Development, 2020)
COVID-19 was declared by the World Health Organization (WHO) as a pandemic in March 2020. Studies so far report that pregnant women appear to be no more prone to infection than the general population. Limited information is available on the effects of the infection on mothers and newborns. Pregnancy itself produces some changes in the immune system and the response to viral infections in general can cause more serious symptoms. Thus, the present study sought to describe the main points related to pregnant women infected with COVID-19, showing from the prevalence to the main complications. This is an integrative literature review, of an exploratory nature, with a qualitative approach, carried out from April to June 2020. For the accomplishment of this study, the following databases were consulted: Medical Literature Analysis and Retrieval System Online (MEDLINE), Google Scholar and Scientific Eletronic Library Online (SCIELO). The Health Sciences Descriptors (DeCS) were used in an associated way: Complications, Obstetrics, COVID-19, Pregnancy and Coronavirus Infections. A total of 8 articles were retrieved by the search strategies, which were analyzed and discussed in full. There is no evidence that the risk of contracting COVID-19 is greater in a pregnant woman than in the general population. However, it is also not known exactly the frequency of infection in pregnant women because, in general, there was no screening in the absence of symptoms.